Pengaruh Perspektif Kemudahan Penggunaan Terhadap Loyalitas Pelanggan dengan Kepuasan sebagai Variabel Mediasi (Studi pada pengguna Game Online Mobile Legends : Bang-Bang di Kota Samarinda) - Ivan Firdaus; Dw Martiyanti (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of perceived ease of use on customer loyalty with customer satisfaction as a mediating variable among Mobile Legends: Bang-Bang online game users in Samarinda City. This study employed a quantitative approach using a survey method by distributing questionnaires to 130 respondents who were active Mobile Legends users in Samarinda City. The sampling technique used was purposive sampling with the criteria that respondents actively played at least two matches per week. Data analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results of this study indicate that perceived ease of use has a positive and significant effect on customer satisfaction. Perceived ease of use also has a positive and significant effect on customer loyalty. In addition, customer satisfaction was proven to have a positive and significant effect on customer loyalty. This study also found that customer satisfaction is able to mediate the relationship between perceived ease of use and customer loyalty among Mobile Legends: Bang-Bang users in Samarinda City. The findings of this study imply that the easier a game is to use, the higher the level of user satisfaction and loyalty toward the game. Therefore, game developers need to pay attention to the aspect of ease of use in order to increase user satisfaction and maintain customer loyalty.